Rimantadine pharmacokinetics after single and multiple doses. - Wills, R J (1987)
Twenty-four healthy adult male volunteers were randomly assigned to one of two rimantadine regimens. The 12 volunteers assigned to regimen 1 orally received a single 100-mg rimantadine tablet followed 5 days later by 100 mg of rimantadine twice a day for 10 days. Volunteers assigned to regimen 2 ingested a single 100-mg rimantadine tablet followed 5 days later by 100 mg once a day for 10 days. The results of the study suggest that the pharmacokinetics of rimantadine are linear and accumulation of the drug during repetitive multiple doses is predictable.